Digital Media in Sports Organizations: The Mediator Role of Social Media Addiction in FoMO and Compulsive Online Shopping - Ayse Demir,; Arif Cetin, (Journal of Educational Issues, 2024)
The impact of communication on individuals and the masses is undeniable. Now, every domain of daily life is influenced by the power of communication thanks to developing technology. The present study aimed to explore the relationship between fear of missing out (FoMO) and compulsive online shopping and investigate the mediator role of social media addiction on this relationship. The sample consisted of randomly selected 205 sports volunteers, 77 females (37.6%) and 128 males (62.4%), taking part in the 16th NKolay Istanbul Half Marathon on April 4, 2021. We collected the data using the “Fear of Missing Out” scale (FoMOS) consisting of 10 items within a subscale, the “Social Media Addiction” scale (SMAS) composed of 20 items within two subscales, and the “Compulsive Online Shopping” scale (COSS) consisting of 28 items within five subscales. We sought answers for seven hypotheses in the study employing a correlational design. The results confirmed our three hypotheses, partially confirmed two hypotheses, rejected the other two hypotheses. We determined that the SMAS were positively correlated with the FoMOS and the COSS. In addition, the FoMOS was positively correlated with the COSS. On the other hand, we concluded that social media addiction partially mediated the relationship between fear of missing out (FoMO) and compulsive online shopping among our participants. While virtual communication had a mediating effect on this relationship, it was not the case for virtual tolerance.